Hippocampal synaptic failure is an early event in experimental parkinsonism with subtle cognitive deficit - Belloso-Iguerategui, Arantzazu; Zamarbide, Marta; Merino-Galan, Leyre; Rodríguez-Chinchilla, Tatiana; Gago, Belén; Santamaria, Enrique; Fernández-Irigoyen, Joaquín; Cotman, Carl W; Prieto, G Aleph; Quiroga-Varela, Ana; Rodríguez-Oroz, María Cruz (Brain (London, England : 1878), 2023)
Learning and memory mainly rely on correct synaptic function in the hippocampus and other brain regions. In Parkinson’s disease, subtle cognitive deficits may even precede motor signs early in the disease. Hence, we set out to unravel the earliest hippocampal synaptic alterations associated with human α-synuclein overexpression prior to and soon after the appearance of cognitive deficits in a parkinsonism model. We bilaterally injected adeno-associated viral vectors encoding A53T-mutated human α-synuclein into the substantia nigra of rats, and evaluated them 1, 2, 4 and 16 weeks post-inoculation by immunohistochemistry and immunofluorescence to study degeneration and distribution of α-synuclein in the midbrain and hippocampus. The object location test was used to evaluate hippocampal-dependent memory. Sequential window acquisition of all theoretical mass spectrometry-based proteomics and fluorescence analysis of single-synapse long-term potentiation were used to study alterations to protein composition and plasticity in isolated hippocampal synapses. The effect of L-DOPA and pramipexole on long-term potentiation was also tested. Human α-synuclein was found within dopaminergic and glutamatergic neurons of the ventral tegmental area, and in dopaminergic, glutamatergic and GABAergic axon terminals in the hippocampus from 1 week post-inoculation, concomitant with mild dopaminergic degeneration in the ventral tegmental area. In the hippocampus, differential expression of proteins involved in synaptic vesicle cycling, neurotransmitter release and receptor trafficking, together with impaired long-term potentiation were the first events observed (1 week post-inoculation), preceding cognitive deficits (4 weeks post-inoculation). Later on, at 16 weeks post-inoculation, there was a deregulation of proteins involved in synaptic function, particularly those involved in the regulation of membrane potential, ion balance and receptor signalling. Hippocampal long-term potentiation was impaired before and soon after the onset of cognitive deficits, at 1 and 4 weeks post-inoculation, respectively. L-DOPA recovered hippocampal long-term potentiation more efficiently at 4 weeks post-inoculation than pramipexole, which partially rescued it at both time points. Overall, we found impaired synaptic plasticity and proteome dysregulation at hippocampal terminals to be the first events that contribute to the development of cognitive deficits in experimental parkinsonism. Our results not only point to dopaminergic but also to glutamatergic and GABAergic dysfunction, highlighting the relevance of the three neurotransmitter systems in the ventral tegmental area-hippocampus interaction from the earliest stages of parkinsonism. The proteins identified in the current work may constitute potential biomarkers of early synaptic damage in the hippocampus and hence, therapies targeting these could potentially restore early synaptic malfunction and consequently, cognitive deficits in Parkinson’s disease.